Multidimensional Scaling Approach For Sustainable Tourism Development In Banyumas Regency - Damar Jati; Tri Esti Masita; Arkham Fadliansyah; Puji Rachmawati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study uses the Multi-Dimensional Scaling (MDS) method to analyze the sustainability status of five waterfall tourist destinations in Banyumas Regency and to guide future development strategies. This study is very important, given the limited research on the sustainability of Curug tourism, which faces challenges such as a declining number of visitors and a low economic contribution to Regional Original Revenue (PAD), at only 6.3%. Using five dimensions—Ecology, Economic, Socio-Cultural, Legal and Institutional, and Infrastructure and Technology—key findings show that overall sustainability status is in the